Disturbed T Cell Signaling and Altered Th17 and Regulatory T Cell Subsets in the Pathogenesis of Systemic Lupus Erythematosus - Rother, Nils; van der Vlag, Johan (Frontiers in Immunology, 2015)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the presence of autoantibodies against nuclear components. Circulating immune complexes of chromatin and autoantibodies deposit in various tissues leading to inflammation and tissue damage. It has been well documented that autoimmunity in SLE depends on autoreactive T cells. In this review, we summarize the literature that addresses the roles of T cell signaling, and Th17 and regulatory T cells (Tregs) in the development of SLE. T cell receptor (TCR) signaling appears to be aberrant in T cells of patients with SLE. In particular, defects in the TCRζ chain, Syk kinase, and calcium signaling molecules have been associated with SLE, which leads to hyperresponsive autoreactive T cells. Furthermore, in patients with SLE increased numbers of autoreactive Th17 cells have been documented, and Th17 cells appear to be responsible for tissue inflammation and damage. In addition, reduced numbers of Tregs as well as Tregs with an impaired regulatory function have been associated with SLE. The altered balance between the number of Tregs and Th17 cells in SLE may result from changes in the cytokine milieu that favors the development of Th17 cells over Tregs.